Intervening effectively with drug abusers infected with HIV: taking into account the potential for cognitive impairment. - Copenhaver, Michael; Avants, S Kelly; Warburton, Lara A; Margolin, Arthur (Journal of psychoactive drugs, 2003)
HIV-positive drug users play a significant role in the transmission of HIV infection. Substance abuse treatment programs can potentially reduce transmission by providing HIV preventive interventions to these individuals. However, there is growing evidence suggesting that, due to a variety of factors, a substantial proportion of HIV-positive drug users may enter addiction treatment with some degree of cognitive impairment in domains that could impede their ability to learn, retain, and execute HIV preventive behaviors. Hence, in order to optimize the effectiveness of these interventions, the client's level of cognitive functioning may need to be considered. In this article an Information-Motivation-Behavioral Skills model of HIV preventive behavior is used to illustrate ways in which impairment in cognitive functioning could impede HIV preventive efforts, and present several practical strategies that front-line substance abuse counseling staff and other treatment providers can incorporate into interventions delivered to HIV-positive clients.
Keywords: Cognition Disorders; HIV Infections; Humans; Risk-Taking; Substance-Related Disorders